Do Listed Real-Estate Companies Trade at a Discount to Their Net Asset Value? - Kjærland, Frode; Lutdal, Erik (Archives of Business Research, 2019)
Listed real estate companies trading at a discount or premium to their net asset value has been an interesting field of study for financial analysts. Previous studies have found several company-specific variables that could potentially explain why market values are above or below the companies’ underlying net asset value. However, different studies often have conflicting and inconsistent results. Hence, the close-end fund puzzle still has many unanswered questions concerning which characteristics affect the pricing in today’s market. We perform a cross-sectional study of 67 listed real estate companies from Norway, Sweden, Denmark, Finland, Germany, the Netherlands, Belgium and the UK based on the fiscal year 2017. We introduce new independent variables as yield requirements used on the property portfolio, occupancy rate, interest rate on debt, average remaining lease term with tenants, EPRA-reporting and interest coverage ratio. Our findings indicate that size, shopping malls, commercial buildings, equity ratio and interest rate are positively correlated with discount to net asset value, while diversification, earnings, interest coverage ratio, REIT status and EPRA-reporting are negatively correlated with discount to net asset value.